2020
DOI: 10.1073/pnas.1912776117
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of current and future large dams on the geographic range connectivity of freshwater fish worldwide

Abstract: Dams contribute to water security, energy supply, and flood protection but also fragment habitats of freshwater species. Yet, a global species-level assessment of dam-induced fragmentation is lacking. Here, we assessed the degree of fragmentation of the occurrence ranges of ∼10,000 lotic fish species worldwide due to ∼40,000 existing large dams and ∼3,700 additional future large hydropower dams. Per river basin, we quantified a connectivity index (CI) for each fish species by combining its occurrence range wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
176
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(179 citation statements)
references
References 51 publications
2
176
0
1
Order By: Relevance
“…At the global scale, our existing understanding of instream infrastructure impacts on sociohydrology and ecology are skewed toward those caused by larger infrastructure such as dams (see Grill et al, 2017; Liermann et al, 2012), but we increasingly understand that smaller infrastructure are more numerous and likely to have greater cumulative changes on our river ecosystems that remain poorly understood (Couto & Olden, 2018; Csiki & Rhoads, 2010; Januchowski‐Hartley et al, 2013; Lange et al, 2019). By mapping infrastructure that does not create large reservoirs behind it, spatially explicit data sets like GROD will enable both finer‐resolution analyses and better understanding of impacts caused by instream infrastructure on hydrological flow alterations (Poff & Hart, 2002), geographic range connectivity for species, particularly fishes (sensu Barbarossa et al, 2020), and important fisheries resources (sensu Carvajal‐Quintero et al, 2017). Equally, GROD will enable spatially explicit scenarios and potential solutions for restoring hydrological and ecological connectivity through the remediation (fish passages and structure modifications) or removal of existing infrastructure along global river networks (sensu Hermoso et al, 2018, Neeson et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…At the global scale, our existing understanding of instream infrastructure impacts on sociohydrology and ecology are skewed toward those caused by larger infrastructure such as dams (see Grill et al, 2017; Liermann et al, 2012), but we increasingly understand that smaller infrastructure are more numerous and likely to have greater cumulative changes on our river ecosystems that remain poorly understood (Couto & Olden, 2018; Csiki & Rhoads, 2010; Januchowski‐Hartley et al, 2013; Lange et al, 2019). By mapping infrastructure that does not create large reservoirs behind it, spatially explicit data sets like GROD will enable both finer‐resolution analyses and better understanding of impacts caused by instream infrastructure on hydrological flow alterations (Poff & Hart, 2002), geographic range connectivity for species, particularly fishes (sensu Barbarossa et al, 2020), and important fisheries resources (sensu Carvajal‐Quintero et al, 2017). Equally, GROD will enable spatially explicit scenarios and potential solutions for restoring hydrological and ecological connectivity through the remediation (fish passages and structure modifications) or removal of existing infrastructure along global river networks (sensu Hermoso et al, 2018, Neeson et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…60% of the world's land surface, and 9 out of 14 of the world's terrestrial biomes, have already fallen below a safe planetary boundary threshold. To fully understand how much of the hydropower potential could be used without substantially damaging the surrounding biodiversity, other biodiversity impact pathways such as impacts of discharge regulation 19 , habitat fragmentation 40 or water regulation in the reservoir 61 should be considered as well.…”
Section: Discussionmentioning
confidence: 99%
“…refs. 2 , 11 , 18 , 40 43 ) have assessed how hydropower electricity production can affect the state of the environment, only a few studies have quantified the resulting biodiversity impacts on a global scale (e.g. refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, more than 50% of rivers globally are impacted by physical infrastructure (e.g., dams, weirs, and culverts) that disrupt the longitudinal connectivity and obstruct sh from accessing essential habitats and resources. Numerous studies have demonstrated the negative eect that articial barriers have on migratory (Catalano et al, 2007;Lucas et al, 2009;Gough et al, 2018;O'Hanley et al, 2020) and resident sh populations (Nislow et al, 2011), including restricted range, altered population structure, reduced spawning and recruitment success, genetic isolation, and local extinction (Woord et al, 2005;Nunn and Cowx, 2012;Barbarossa et al, 2020;Pereira et al, 2020). This, in turn, can compromise the ability of river ecosystems to deliver the full range of ecosystem services (Rounsevell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%